The Development of a Differentiated Workbook Based on Students’ Learning Styles: An Evaluation of Its Validity, Practicality, and Effectiveness - Anggraini, Hesti Wahyuni; Zuraida, Zuraida; Maharrani, Dwi (Edukasi, 2025)
A variety of differentiated approach students’ worksheets depict pivotal role to support meaningful and interesting English language learning. Through the application of developmental research, this study aimed at designing and developing the feasibility of a differentiated-based workbook to improve students’ reading comprehension skills. The developed product was expected to meet the students’ needs in accordance with their learning styles. This study was conducted at Faculty of Teacher Training and Education, Sriwijaya University, Indonesia, by applying a model by Akker (1999), which involves the phases of analysis, design, evaluation and revision modified by Tessmer (1993). A model by O’Brein (1985) was also used to identify students’ learning styles, namely visual, auditory, and kinesthetic learners. Questionnaire, test and interview were delivered to gain the data from 38 students, in which three participants in one-to-one evaluation, nine students in small group evaluation, and 26 participants in field test. Content validity demonstrated high validity, with the average score of 4,15. Through the construct validity, the workbook had high validity with the average score of 4,65 while technology validity proved its validity with revision in the average score of 4,4. The one-to-one evaluation included three students, with one student exemplifying three distinct learning styles, achieving an average score of 3.8. The practicality and effectiveness of this developed workbook based on learning styles showed excellent result with the average score of 4.16. In summary, differentiated approach-based students’ worksheet can be used to teach and improve students’ reading comprehension skills.